Bone marrow ribonucleotide reductase mRNA levels and methylation status as prognostic factors in patients with myelodysplastic syndrome treated with 5-Azacytidine. Issue 3 (23rd February 2022) - Kontandreopoulou, Christina-Nefeli; Diamantopoulos, Panagiotis T.; Giannopoulos, Andreas; Symeonidis, Argiris; Kotsianidis, Ioannis; Pappa, Vasiliki; Galanopoulos, Athanasios; Panayiotidis, Panayiotis; Dimou, Maria; Solomou, Elena; Loupis, Theodoros; Zoi, Katerina; et al.
Abstract: Ribonucleotide Reductase (RNR) is a two-subunit (RRM1, RRM2) enzyme, responsible for the conversion of ribonucleotides to deoxyribonucleotides required for DNA replication. To evaluate RNR as a biomarker of response to 5-azacytidine, we measured RNR mRNA levels by a quantitative real-time PCR in bone marrow samples of 98 patients with myelodysplastic syndrome (MDS) treated with 5-azacytidine with parallel quantification of the gene promoter's methylation. Patients with low RRM1 levels had a high RRM1 methylation status ( p  = 0.005) and a better response to treatment with 5-azacytidine ( p  = 0.019). A next-generation sequencing for genes of interest in MDS was also carried out in a subset of 61 samples. Splicing factor mutations were correlated with lower RRM1 mRNA levels ( p  = 0.044). Our results suggest that the expression of RNR is correlated with clinical outcomes, thus its expression could be used as a prognostic factor for response to 5-azacytidine and a possible therapeutic target in MDS.